HEMODYNAMICS CHANGES IN CHILDREN WITH SEPSIS - Shadrin, V.O.; Yevtushenko, V.V. (The Ukrainian Scientific Medical Youth Journal, 2017)
Sepsis is one of the most common causes of mortality in children. The severe course of sepsis is usually associated with the development of septic shock and multiple organ failure. An important component in the comprehensive examination and evaluation of treatment effectiveness is the monitoring of hemodynamic parameters. We aimed to evaluate changes in central and peripheral hemodynamics by echocardiography and doppler ultrasound in children with sepsis. Material and methods. A retrospective study of cases of septic shock in children aged 0 to 18 years who underwent treatment in the intensive care unit was conducted. Patients were monitored for central and peripheral hemodynamics by echocardiography and doppler ultrasound. Results. 108 cases of sepsis were investigated. Meningococcus was an etiological factor in 53,7% patients, 0.9% – Staphylococcus, 0.9% – Pneumococcus, 0,9% – Yersinia, and in 41,7% aetiology was not been established. In 12 children from the study group fatal outcome was occurred. Septic shock development was associated with significantly higher rates of heart rate (HR) and an increase in peripheral resistance (RI) indices in the abdominal trunk and renal arteries. Fatal course of the disease was associated with a high rate of heart rate and a decrease in diastolic velocity (V min) in the abdominal trunk and renal arteries. Conclusion. Echocardiography and ultrasound dopplerography in children with sepsis are the useful tools to evaluate the pattern and extent of cardiovascular dysfunction. Results of regional blood flow assessment can be a diagnostic criterion for the septic shock and has prognostic value in children with sepsis.